Educational upgrading, structural change and the task composition of jobs in Europe1. Issue 2 (21st February 2018) - Hardy, Wojciech; Keister, Roma; Lewandowski, Piotr
Abstract: We analyze the changes in the task content of jobs in 24 European countries between 1998 and 2015. We link the O*NET occupational data with the European Union Labour Force Survey (EU‐LFS), and use the methodology of Acemoglu and Autor (2011 ). We find that the intensity of non‐routine cognitive tasks grew in all countries, while the intensity of manual tasks declined. Workforce upskilling was the major factor contributing to these developments. The intensity of routine cognitive tasks grew in most Central and Eastern European countries, but it declined in Western European countries. This difference is attributed to the contrasting patterns of structural changes in these groups of countries.